Target of Rapamycin Regulates Genome Methylation Reprogramming to Control Plant Growth in Arabidopsis - Zhu, Tingting; Li, Linxuan; Feng, Li; Mo, Huijuan; Ren, Maozhi (Frontiers in Genetics, 2020)
DNA methylation is an indispensable epigenetic modification that dynamically regulates gene expression and genome stability during cell growth and development processes. The target of rapamycin (TOR) has emerged as a central regulator to regulate many fundamental cellular metabolic processes from protein synthesis to autophagy in all eukaryotic species. However, little is known about the functions of TOR in DNA methylation. In this study, the synergistic growth inhibition of Arabidopsis seedlings can be observed when DNA methylation inhibitor azacitidine was combined with TOR inhibitors. Global DNA methylation level was evaluated using whole-genome bisulfite sequencing (WGBS) under TOR inhibition. Hypomethylation level of whole genome DNA was observed in AZD-8055 (AZD), rapamycin (RAP) and AZD+RAP treated Arabidopsis seedlings. Based on functional annotation and KEGG pathway analysis of differentially methylated genes (DMGs), most of DMGs were enriched in carbon metabolism, biosynthesis of amino acids and other metabolic processes. Importantly, the suppression of TOR caused the change in DNA methylation of the genes associated with plant hormone signal transduction, indicating that TOR played an important role in modulating phytohormone signals in Arabidopsis. These observations are expected to shed light on the novel functions of TOR in DNA methylation and provide some new insights into how TOR regulates genome DNA methylation to control plant growth.